FRI0363 KL6 and not CCL-18 is a predictor of early progression in systemic sclerosis related interstitial lung disease. (15th June 2017) - Salazar, G; Kuwana, M; Wu, M; Estrada-Y-Martin, RM; Ying, J; Charles, J; Bellocchi, C; Mayes, M; Assassi, S
Abstract : Background: Pneumoproteins are attractive biomarker candidates in systemic sclerosis (SSc) related interstitial lung disease (ILD) because they are easily obtainable and lung-specific. KL-6 and CCL-18 (PARC) have been previously reported as promising predictive biomarkers of lung parenchymal damage in multiple disorders including SSc-ILD. Objectives: Our goal was to determine the predictive significance of these two pneumoproteins for forced vital capacity % (FVC) decline within the first year of follow-up in patients with early SSc-ILD, in order to inform individualized care in routine clinical practice and facilitate enrichment strategies in clinical trials. Methods: GENISOS (Genetics versus ENvironment In Scleroderma Outcome Study) cohort patients who had ILD verified by imaging and available pulmonary function tests at enrollment plus 12–18 months thereafter, were included in this study. All patients had disease duration ≤5 years at enrollment. FVC, expressed as percentage of predicted value was used as surrogate for severity of ILD. Annualized percent change in FVC at one year follow up was calculated. Baseline demographic, clinical variables and two pneumo-proteins, KL-6 and CCL-18 were investigated. KL-6 and CCL-18 were measured in the plasma by commercially available, validated ELISA kits. Linear regression with baseline clinical and demographic variables as independent variables was performed in univariable and multivariable models. Only variables that reached p<0.1 were included in the multivariable analyses. Results: A total of 82 patients with early SSc-ILD were included, 18 were male and 45 had diffuse cutaneous involvement. Mean disease duration was 2.3 years. Rate of FVC% predicted change over time ranged from -0.23 to 0.38, indicating a highly variable course. Baseline KL-6 levels were higher in patients than healthy controls (p<0.0001). Baseline higher KL-6 levels were predictive of faster FVC% decline at the one year follow-up (b=-0.03, p =0.04). Upon categorizing KL-6 using a previously determined optimal cut-off of 1273 u/mL (1), its predictive significance remained in the univariate (p=0.01) and multivariable analyses adjusted for Scl-70, disease type and gender (b=-0.03, p =0.04). Twenty nine (34.5%) patients had KL6 levels equal or above 1273 u/mL. Although CCL-18 was higher in patients than controls (<0.0001), its levels did not predict rate of FVC decline (provide p-value) Conclusions: KL-6 but not CCl-18 is predictive of early SSc-ILD progression. In this study, we also validated the previously proposed cut-off of 1273 for KL-6 in an independent cohort. KL-6 is a promising pneumoprotein that can inform individualized clinical care and contribute to enrichment strategies in clinical trials of SSc-ILD. References: Kuwana M, Shirai Y, Takeuchi T. Elevated Serum Krebs von den Lungen-6 in Early Disease Predicts Subsequent Deterioration of Pulmonary Function in Patients with Systemic Sclerosis and Interstitial Lung Disease. J Rheumatol 2016. Acknowledgements: This study was funded by the National Institute of Health NIH/NIAMS K23 AR061436 (Assassi); NIH/NIAMS P50-AR05414 and the Department of Defense Congressionally Directed Medical Research Programs (W81XWH-07–01–0111- Mayes). Disclosure of Interest: None declared